Visual field preferences of object analysis for grasping with one hand - Le, Ada; Niemeier, Matthias (Frontiers in Human Neuroscience, 2014)
When we grasp an object using one hand, the opposite hemisphere predominantly guides the motor control of grasp movements (Davare et al. 2007; Rice et al. 2007). However, it is unclear whether visual object analysis for grasp control relies more on inputs (a) from the contralateral than the ipsilateral visual field, (b) from one dominant visual field regardless of the grasping hand, or (c) from both visual fields equally. For bimanual grasping of a single object we have recently demonstrated a visual field preference for the left visual field (Le and Niemeier 2013a, 2013b), consistent with a general right-hemisphere dominance for sensorimotor control of bimanual grasps (Le et al., 2013). But visual field differences have never been tested for unimanual grasping. Therefore, here we asked right-handed participants to fixate to the left or right of an object and then grasp the object either with their right or left hand using a precision grip. We found that participants grasping with their right hand performed better with objects in the right visual field: maximum grip apertures (MGAs) were more closely matched to the object width and were smaller than for objects in the left visual field. In contrast, when people grasped with their left hand, preferences switched to the left visual field. What is more, MGA scaling showed greater visual field differences compared to right-hand grasping. Our data suggest that, visual object analysis for unimanual grasping shows a preference for visual information from the ipsilateral visual field, and that the left hemisphere is better equipped to control grasps in both visual fields.